2014
DOI: 10.1242/jeb.109736
|View full text |Cite
|
Sign up to set email alerts
|

Unpredictable chronic stress decreases inhibitory avoidance learning in Tuebingen Long-Fin zebrafish (Danio rerio Hamilton): stronger effects in the resting phase than in the active phase

Abstract: Zebrafish (Danio rerio Hamilton) are increasingly used as a model to study the effects of chronic stress on brain and behaviour. In rodents, unpredictable chronic stress (UCS) has a stronger effect on physiology and behaviour during the active phase than during the resting phase. Here, we applied UCS during the daytime (active phase) for 7 and 14 days or during the night-time (resting phase) for 7 nights in an in-house-reared Tuebingen long-fin (TLF) zebrafish strain. Following UCS, inhibitory avoidance learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 79 publications
(118 reference statements)
4
57
0
Order By: Relevance
“…We demonstrated for the first time that UCS protocol induced several changes in redox homeostasis in the zebrafish brain and revealed that EE has a protective effect against the oxidative stress induced by the UCS protocol. UCS protocol induces several biochemical changes in the zebrafish brain and through sustained activation of the neuroendocrine axis leads to increased cortisol levels (Piato et al, 2011;Manuel et al, 2014;Marcon et al, 2016;Rambo et al, 2017;Song et al, 2017). This was confirmed by the results recently published in our previous study, which showed that the UCS protocol increased cortisol levels while EE for 21 or 28 days prevented this increase (Marcon et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…We demonstrated for the first time that UCS protocol induced several changes in redox homeostasis in the zebrafish brain and revealed that EE has a protective effect against the oxidative stress induced by the UCS protocol. UCS protocol induces several biochemical changes in the zebrafish brain and through sustained activation of the neuroendocrine axis leads to increased cortisol levels (Piato et al, 2011;Manuel et al, 2014;Marcon et al, 2016;Rambo et al, 2017;Song et al, 2017). This was confirmed by the results recently published in our previous study, which showed that the UCS protocol increased cortisol levels while EE for 21 or 28 days prevented this increase (Marcon et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Zebrafish (Danio rerio) has emerged as a model system in behavioral neuroscience and is used to study social stress (Giacomini et al, 2016), major depressive disorders (Manuel et al, 2014;Fonseka et al, 2016), and aggression (Paull et al, 2010; Oliveira et al, 2011), and their social behaviors have been well described (Dahlbom et al, 2012). When paired, zebrafish interact aggressively with ritualized displays that increase in intensity until a social dominance emerges.…”
Section: Introductionmentioning
confidence: 99%
“…Piato and colleagues [17] showed that UCS protocol increased the anxiety and cortisol levels in zebrafish, triggering neuroendocrine disturbances. In addition, UCS promoted an increase of cortisol levels, which could have an important neuromodulatory role in the regulation of neuronal function in the brain, affecting behavior and cognition [6,17]. Studies have demonstrated that corticosteroid hormones interact with various neurotransmitter systems, including purinergic system.…”
Section: Discussionmentioning
confidence: 99%
“…The shortterm-period stress response is beneficial to an organism because it improves the chances of the individual for survival [5]. However, unpredictable chronic stress (UCS) affects physiological [6,7], immunological [8,9], endocrine [10,11], and developmental processes [12,13]. UCS changes brain physiology and neural circuits [14] and leads to the development of depressive behaviors [15].…”
Section: Introductionmentioning
confidence: 99%